2017
DOI: 10.1371/journal.pone.0186923
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of acute and convalescent illness of confirmed chikungunya cases from Chiapas, S. Mexico: A cross sectional study

Abstract: BackgroundThe emerging chikungunya virus (CHIKV), is an arbovirus causing intense outbreaks in North America. The situation in Mexico is alarming, and CHIKV threatens to spread further throughout North America. Clinical and biological features of CHIKF outbreaks in Mexico have not been well described; thus, we conducted a cross sectional study of a CHIKV outbreak in Chiapas, Southern Mexico to further characterize these features.Methodology/Principal findingsWe collected blood samples from patients suspected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
7
20
0
Order By: Relevance
“…As noted above, our clinical staff was convinced that the AFI peak seen in October and November 2014 ( Figure 2) reflected a "recurrence" of CHIKV; in actuality, it built on a DENV1 case cluster, with some ZIKV mixed in at the end, and a still unidentified presumptive pathogen responsible for the majority of cases. Although we recognize the difficulties inherent in making clinical arboviral diagnoses, our data reinforce the frequency with which arthralgias are seen in CHIKV cases (with knees, wrists, and ankles most commonly affected, in keeping with findings in studies in other locales [9,30]).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As noted above, our clinical staff was convinced that the AFI peak seen in October and November 2014 ( Figure 2) reflected a "recurrence" of CHIKV; in actuality, it built on a DENV1 case cluster, with some ZIKV mixed in at the end, and a still unidentified presumptive pathogen responsible for the majority of cases. Although we recognize the difficulties inherent in making clinical arboviral diagnoses, our data reinforce the frequency with which arthralgias are seen in CHIKV cases (with knees, wrists, and ankles most commonly affected, in keeping with findings in studies in other locales [9,30]).…”
Section: Discussionsupporting
confidence: 83%
“…As has been noted in multiple studies [8,22,23,[30][31][32], it can be difficult, particularly in endemic regions, to identify an infecting arbovirus based solely on clinical presentation. The current study made use of a school cohort, and consequently ages were concentrated between 3 years and 20 years, reflecting attendance in prekindergarten through "grade 13" (an additional year of school generally taken as part of the secondary education cycle).…”
Section: Discussionmentioning
confidence: 99%
“…Like other studies, we found symmetrical arthralgia to be a frequent symptom in patients with suspicion of CHIKV infection [30,33,6062]. Knees, hands and ankles the most affected joints [30,33,60,6264]. However only arthritis was statistically significant in true positive patients when compared to the other three groups (false positives, false negatives and true negatives).…”
Section: Discussionsupporting
confidence: 79%
“…Other studies found similar percentages of fever ranging from 90 to 100%, however we have to remember that it is an obligatory symptom for WHO CHIKV infection criteria, increasing selection bias [30,33,75,49,53,54,63,64,7274]. Another point to consider is that in regions where Zika, Dengue or CHIKV infections can co-exist at the same time, the use of non-specific symptoms like fever in the diagnostic criteria, increases sensibility but decreases specificity reducing the ability to discern which infection is responsible, leading to over or underdiagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the C-reactive protein is generally elevated in the acute phase illness (Table 2) (Venugopalan et al, 2014;Brito and Cordeiro, 2016;PAHO, 2017). Elevation of hepatic enzymes, as well as elevated creatinine and creatine phosphokinase levels, have also been reported (Danis-Lozano et al, 2017). The different laboratory patterns observed during CHIKV, DENV and ZIKV infections, added to clinical findings, may be incorporated to support a correct diagnosis (Tables 1 and 2).…”
Section: Laboratory Diagnosticmentioning
confidence: 97%